Ramadan during MCO, A Blessing In Disguise - UMP, PNC (2020)
Kuantan, 6 May 2020 - Muslims in this country and all around the globe will be practicing Ramadan in the new normal situation, due to the implementation of Movement Control Order (MCO) following the spread of COVID-19 pandemic.